A Case Report of Acute Airway Compromise due to Subcutaneous Emphysema - David Olmstead; Gary Gelfand; Ian Anderson; John B. Kortbeek (Case Reports in Medicine)
In the acute management of a trauma patient, airway patency is of utmost importance. The present case describes a male patient who presented with delayed severe upper airway obstruction secondary to massive subcutaneous emphysema following blunt traumatic injury two days previously. Airway compromise is a rarely described but serious complication of subcutaneous emphysema. Current management of subcutaneous emphysema and its association with pneumothorax is summarized. Early decompression of underlying pneumothoraces in patients with significant subcutaneous emphysema should be performed to avoid this rare complication.